Optimizing Weed Control: A Study on the Influence of Drone Sprayer Altitude in Herbicide Application - Musrian, Teuku; Aninditya, Mas Wisnu; Nurcholis, Jati (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
This research aims to determine the spraying distance of herbicides using a drone sprayer to achieve effective weed control. The use of herbicides is crucial to managing the competition for plant nutrients that threaten crop yields. The study analyzes the herbicide distribution patterns on plants sprayed using a drone with a flying speed of 3 m/s, utilizing a flat fan nozzle at different flying distances. During spraying activities, a compact weather station was employed to record environmental conditions, including air temperatures around 33.4-34.4 °C, relative humidity between 56.2-64.3%, wind speeds of 0.1-1 m/s, and wind direction from the southwest or south. There was no rainfall during the spraying sessions. The research results significantly contribute to the development of herbicide spraying technology using drones by carefully considering environmental conditions. Chlorophyll content was measured using the Soil-Plant Analysis Development (SPAD) chlorophyll meter and the Normalized Difference Vegetation Index (NDVI) through drone mapping. The drone sprayer at a 1-meter distance, covering an area of 600 m2, and using a 10 ml herbicide mixed with 10,000 ml water effectively reduced chlorophyll in weed plants. Multispectral data showed significant changes with a shift to red indicating non-vegetative areas after herbicide spraying. There was a decrease in average chlorophyll values measured at 2, 4, 6, 8, and 10 days post-spraying, with the lowest recorded on plots with a 1-meter spraying distance (average chlorophyll value of 19.62 SPAD). Therefore, the drone sprayer at a 1-meter distance proved effective in controlling weeds and reducing chlorophyll in non-target plants, making a crucial contribution to the development of herbicide spraying technology using drones and improving efficiency in agricultural management.